Implementation of Agile Project Management for Digitalization in the Oil & Gas Industry: A Case Study of Gas Stations in Indonesian Company - Hari Prasetyo Tri Wicaksono; Geri Yesa Ermawan (Green Publisher Indonesia, 2026)
Agile project management has been extensively utilized in software development, but its application in IoT installation and integration projects remains relatively uncommon. This study aims to enhance the implementation of agile project management practices within the context of gas station digitalization, which faced a target completion shift three months early. This acceleration was driven by business-critical factors, including compliance with government regulations, subsidy reimbursements, and operational efficiency improvements. Using a case study and the Design Science Research Methodology (DSRM), the research focuses on an oil and gas company undertaking gas station digitalization to comply with regulatory requirements. The project was managed using agile principles and the Scrumban framework. By adopting agile project management and Scrumban, the company achieved faster deployment cycles, improved real-time data accuracy and coverage, and enhanced coordination between stakeholders, leading to 50% faster integration time per station. As a contribution, the study introduces a project management model tailored for agile adoption and an application of Scrumban to large-scale IoT-based infrastructure projects, particularly in a highly regulated industry such as energy distribution. Unlike previous studies focusing on agile methods in software development, this research extends the methodology to a multi-site, hardware-integrated digital transformation, addressing both technical and operational challenges in real time to facilitate the effective execution of digital transformation initiatives within the oil and gas industry.